Transitions and trajectories in intrinsic capacity states over time: a systematic review - Youting Wang; Nan Tang; Mengqi Shao; Jie Song; Qingqing Su; Yuan Gao (BMC Geriatrics)
Abstract Intrinsic Capacity (IC) is a crucial measure of the comprehensive physiological and psychological capabilities of older adults, playing a key role in assessing healthy aging. This systematic review aims to explore the trajectories of IC in older adults, as well as the associated determinants and health outcomes. By searching through PubMed, Embase, Ovid, and Web of Science databases, we identified 13 studies that met our inclusion criteria. To ensure the rigor of the review, the Newcastle-Ottawa Scale (NOS) critical appraisal tool for cohort studies and the Guidelines for Reporting on Latent Trajectory Studies were employed to assess the quality of the studies included. When IC is represented as a single composite value, there are primarily three trajectory types: declining trajectory (characterized by a sharp, moderate, or mild decline from baseline IC), stable trajectory (little change compared to baseline IC), and high trajectory (high baseline IC with an increasing trend). When IC is broken down into individual dimensions, these trajectories primarily reflect the degree of impairment in different domains and changes in IC status. The trajectories can be divided into robust status (no impaired domains, stable IC status), mild impairment (impairment in 1–2 domains, mild IC impairment), and severe impairment (impairment in multiple domains, severe IC impairment). Factors influencing IC trajectories include age, gender, education level, ethnicity, number of chronic diseases, marital status, perceived financial adequacy, economic assistance status, self-assessed health status, and inflammatory biomarkers (such as IL-6, TNFR-1, and GDF-15). Adverse IC trajectory patterns are associated with increased mortality, quality of life, disability, frailty, and fall risk. Future research should focus on changes in IC at the end of life, increase the number of assessment time points, use objective measurement methods, and consider experimental designs to better understand the mechanisms behind IC trajectories, providing a scientific basis for targeted interventions.